Fresno County Bar Association Old-Timers Luncheon - Watkins, Howard::::::::: (1984)
Howard Thomas talking with Justice Mildred Lillie; Max Hayden checking microphone; Donald Fischbach and Justice Pauline Davis Hanson at head table